Effects of Trace Elements and Vitamins on the Synthesis of Steroid Hormones in Follicular Granulosa Cells of Yak - Yanbing Lou; Tingting Yang; Yanqiu Zhu; Chenglong Xia; Hengmin Cui; Huidan Deng; Yixin Huang; Jing Fang; Zhicai Zuo; Hongrui Guo (Veterinary Sciences)
Yak (Bos grunniens), a special breed of cattle on the Qinghai–Tibet Plateau, has low fertility due to nutritional deficiency, especially the trace elements. The steroid hormones estradiol (E2) and progesterone (P4) synthesized by yak follicular granulosa cells (BGCs) are involved in the entire reproductive process. In the present study, we investigated the effects of trace elements and vitamins on yak follicular GCs, including the cellular activity, the synthesis of E2 and P4, and the expression of genes related to steroid hormone synthesis. The results showed that moderate supplementation of vitamin D3 (VD3), strontium (Sr), manganese (Mn), and selenium (Se) enhanced granulosa cell activity. Within the safe dose range, the addition of vitamin A (VA), VD3, cobalt (Co), Sr, copper (Cu), Mn, Se, and chromium (Cr) significantly increased the synthesis of E2 by GCs, while the addition of VA, vitamin C (VC), VE, zinc (Zn), Sr, Cu, and Cr enhanced the production of P4 in GCs. The changes in steroid synthesizing genes were consistent with the changes in hormone synthesis. This study provides an experimental basis for the addition of trace elements to improve the production performance of yaks.